2021
DOI: 10.1128/mbio.01777-21
|View full text |Cite|
|
Sign up to set email alerts
|

Signatures of COVID-19 Severity and Immune Response in the Respiratory Tract Microbiome

Abstract: COVID-19, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection of the respiratory tract, results in highly variable outcomes ranging from minimal illness to death, but the reasons for this are not well understood. We investigated the respiratory tract bacterial microbiome and small commensal DNA viruses in hospitalized COVID-19 patients and found that each was markedly abnormal compared to that in healthy people and differed from that in critically ill patients without COVID-19.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
95
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(129 citation statements)
references
References 44 publications
15
95
1
Order By: Relevance
“…The SARS-CoV-2-induced URT microbiome dysbiosis itself, rather than consistent changes in specific bacterial taxa, could be associated with an increased risk of severe disease. However, while the overall antibiotic usage in our study was low, in other manuscripts examining the association of respiratory microbiome with COVID-19 severity, patient antibiotic use was either not reported ( Mostafa et al., 2020 ; Rueca et al., 2021 ; Ventero et al., 2021 ), reported as high in all groups ( Merenstein et al., 2021 ), or reported as highest in patients with the most severe COVID-19 ( Hernández-Terán et al., 2021 ; Li et al., 2021 ). Potentially, dysbiosis in some patients could be linked to administration of antibiotics rather than the SARS-CoV-2 infection.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…The SARS-CoV-2-induced URT microbiome dysbiosis itself, rather than consistent changes in specific bacterial taxa, could be associated with an increased risk of severe disease. However, while the overall antibiotic usage in our study was low, in other manuscripts examining the association of respiratory microbiome with COVID-19 severity, patient antibiotic use was either not reported ( Mostafa et al., 2020 ; Rueca et al., 2021 ; Ventero et al., 2021 ), reported as high in all groups ( Merenstein et al., 2021 ), or reported as highest in patients with the most severe COVID-19 ( Hernández-Terán et al., 2021 ; Li et al., 2021 ). Potentially, dysbiosis in some patients could be linked to administration of antibiotics rather than the SARS-CoV-2 infection.…”
Section: Discussioncontrasting
confidence: 85%
“…An interpretation of these findings could be that we observed increasing microbiome dysbiosis or destabilization as disease severity increased. Other studies have similarly reported respiratory microbiome dysbiosis in patients with COVID-19 compared with controls ( Engen et al., 2021 ; Merenstein et al., 2021 ) and in those with the most severe disease ( Hernández-Terán et al., 2021 ). SARS-CoV-2-induced instability in the microbiome might make it challenging to identify specific taxa associated with disease severity as the changes could be stochastic and less likely to be shared among different patients, a finding also reported by Li et al., who found that patients with the most severe COVID-19 each had a distinct respiratory microbiome ( Li et al., 2021 ).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…A meta-analysis done by Morens and colleagues of 8,398 autopsies from 1918 to 1919 found that the vast majority had evidence of bacterial pneumonia ( 1 ) and concluded that most were from “common upper respiratory-tract bacteria.” Even as this was from the preantibiotic era, the findings have been foundational knowledge for bacterial–viral copathogenesis. In contrast to general agreement on the importance of bacterial superinfection in influenza infection, the role of bacterial copathogenesis in COVID-19 is less clear ( 2 5 ) and interactions may operate through indirect pathways.…”
mentioning
confidence: 81%